Impact of instituting hard-waiver on a student health insurance program at a public university. Issue 3 (3rd April 2021) - Kim, Joseph; Ngo, Duc Anh; Rege, Saumitra; Tolley, William; Holstege, Christopher
Abstract: Objective: The purpose of this study is to assess the impact of implementing hard-waiver on the student health insurance landscape at a major public university. Methods: Data from two years before (2013–2015) and after (2015–2017) the hard-waiver program was implemented were analyzed descriptively using the university data sources. Results : The university-sponsored insurance group pre-waiver was made up of 4, 850 students, while this group included 9, 002 students after the hard-waiver program was implemented. Approximately 62% of the waived insurance group were White, compared to 47% in the university-sponsored insurance group. The White population who waived the insurance plan was 20% greater than the minority population. The proportion of the White population having a university-sponsored insurance plan was 0.6 times that of the minority population. Conclusions : University-sponsored insurance enrollment increased markedly following the implementation of hard-waiver and impacted various student demographic groups differently.